Responsible Use of Antibiotics in Fish Farming - Rheman, Shafiq; Hossain, Sabrina; Al Mahmud, Abdullah; Hossain, Mohammad Shohorab (WorldFish, 2025)
The leaflet provides practical guidance for fish farmers and veterinary drug sellers on the responsible use of antibiotics in aquaculture. It explains what antibiotics are, outlines the risks of misuse such as treatment failure and AMR, and gives clear do’s and don’ts for both farmers and drug sellers. The key message emphasizes consulting professionals before using medicines, maintaining biosecurity, observing withdrawal periods, and avoiding unapproved or expired drugs. The leaflet concludes that biosecurity and good farm management are the most effective ways to prevent disease, and that prescription-based medicine sales protect both health and business.